Improving Reading Comprehension in Secondary School Students through ICT Tools: An Innovative Approach - Garcia Atoche, Gisella del Carmen (2024)
The research focused on determining the influence of ICT tools in improving reading comprehension in second grade secondary school students. A quantitative approach and a quasi-experimental design were used, with a sample of 74 students divided into two groups: one experimental and one control. A questionnaire validated by experts was applied for data collection and the Jasp program was used for data analysis, using the Mann-Whitney U coefficient. The results showed that reading comprehension improves significantly (p<.05) with a large effect size after the application of ICT tools. It is concluded that reading comprehension is a skill that can be improved through the application of educational programs that incorporate digital tools. These findings suggest the importance of implementing digital technologies in the educational field to improve students' reading comprehension.